Karakterisasi Morfologi Daun Begonia Alam (Begoniaceae): Prospek Pengembangan Koleksi Tanaman Hias Daun di Kebun Raya Indonesia - -M.Siregar, Hartutiningsih; Wahyuni, Sri; Ardaka, I Made (JURNAL BIOLOGI INDONESIA, 2018)
ABSTRACTFoliage ornamental plant is one of popular outdoor and indoor plant, of which is Begonia (Begoniaceae). The aim of this study is to seek the potentions of Indonesia Botanic Garden’s Begonia collections. The study was done by visual observations method by characterizing the morphological leaves of 73 species of native species in the Bogor and Bali Botanic Greenhouses. The qualitative data was obtained by observing the leaf type, shape, margin, apex, base colour, texture, and hairiness, while the quantitative data was collected by measuring the thickness and size of the leaf and petiole lengths. The scoring was assumed by comparing to the popular species, and the score that given is range from 1-3. The result of this study is some of the collection, such as  B. brevirimosa Irmsch. susp. brevirimosa, B. brevirimosa subsp. exotica Tebbitt,  B. goegoensis N.E. Br, B. bipinnatifida J.J.Sm., B. dropiae Ardi, B. holosericeoides Ardi & D.C. Thomas, B. siccacaudata J. Door, B. robusta Blume, B. olivaceae Ardi, B. puspitae Ardi, B. sudjanae Janson dan  B. serratipetala Irmsch have the highest score on the leaves morphological characteristic (shape and colouration), which mean all of these species can be planted as exotic ornamental plants without any hybridization process. It is expected that the listed species as the result of this study can be used as a reference for developing a new cultivars from Indonesian native species. Keywords: Begonia, ornamental  plant, Botanic Gardens of Indonesia